PENERAPAN MANAJEMEN RISIKO HUKUM DALAM AKTIVITAS PERBANKAN - T. Endang Ratnawati (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
Risk is cost of loss that is caused either force majeure or overmacht. Control of law risk in a bank can be fraced foon the causal factors and the offort to control it, therefore the law risk can be minimalized.